The therapeutic potential of antibiotics and probiotics in the treatment of pouchitis. (November 2015) - Gionchetti, Paolo; Calabrese, Carlo; Lauri, Adriano; Rizzello, Fernando
Abstract : Pouchitis is the most frequent long-term complication of pouch surgery for ulcerative colitis. There is consistent evidence on the implication of bacterial flora in the pathogenesis of pouchitis, and there is evidence for a therapeutic role of antibiotics and probiotics in therapy of this disease. Antibiotics, particularly ciprofloxacin and metronidazole, are the mainstay of treatment for acute pouchitis. In chronic refractory pouchitis, after having excluded other diagnoses (infections, Crohn's disease of the pouch, ischemia and irritable pouch), antibiotic combination therapy is the treatment of choice. The highly concentrated probiotic mixture VSL#3 has been shown to be effective in prevention of pouchitis onset and in maintaining antibiotic-induced remission.